Pengaruh Pajak, Intangible Assets, Kepemilikan Asing, Profitabilitas, Mekanisme Bonus terhadap Transfer Pricing - Muhammad Solihin; Sohibunajar Sohibunajar; Ilham Ramadhan Ersyafdi (Accounting Department UNUSIA, 2023)
The policy adopted by the company in determining the transfer price in a transaction, be it services, goods, intangible assets, or other financial transactions, is transfer pricing. Transfer pricing often creates problems, especially those related to taxation. This study aims to find out whether transfer pricing can be influenced by taxes, intangible assets, foreign ownership, profitability and bonus mechanisms for companies listed on the Indonesia Stock Exchange in the consumer non-cyclicals sector and the food and beverage sub-sector for the 2019-2021 period. A sample of 19 companies was selected which was determined using a purposive sampling method. The analytical method used in this study is multiple regression analysis. The results of the study concluded that partially only the tax variable had no influence on transfer pricing while other independent variables had an influence on transfer pricing. Simultaneously, transfer pricing can be influenced by all independent variables. Based on the coefficient of determination, the independent variables are able to explain transfer pricing by 68% and 32% is explained by other variables outside this study.